Clinical and analytical relevance of NNRTIs minority mutations on viral failure in HIV‐1 infected patients. Issue 3 (19th November 2013) - Mohamed, Sofiane; Ravet, Sophie; Camus, Claire; Khiri, Hacène; Olive, Daniel; Halfon, Philippe
Abstract The objective of this study was to assess the analytical and clinical relevance of minority variants using a new pyrosequencing (PSQ) assay and to detect minor variants with frequencies below the current 20% clinical setting limit. A PSQ approach for detecting and quantifying mutations was developed for the analysis of 14 codons of the human immunodeficiency virus (HIV) reverse transcriptase (RT) gene below the limit of conventional sequencing. Ten patients who experienced virological failure (VF) after a first‐line regimen of lamivudine, tenofovir, and either efavirenz, nevirapine, or etravirine, as well as 10 controls patients without VF, were included in this retrospective study. Baseline plasma and plasma from the time of VF were assessed using Sanger sequencing and PSQ methods. The analytical sensitivity for the detection of minor sequence variants is 5%. At baseline, no minority variant was detected in 10/10 patient controls using both the Sanger sequencing and PSQ assays, whereas, two patients who failed therapy had baseline non‐nucleoside reverse transcriptase inhibitor (NNRTI) mutations that were not detected by the standard genotyping. At the time of VF, standard genotyping detected mutations in four out of the 10 VF patients, whereas, PSQ detected mutations in five out of the 10 VF patients. Clinically, minority mutations at a 10% level of detection can be assessed efficiently by pyrosequencing and used as a suitable predictor of the evolution of viral populations. These traits allow for a better interpretation of data analysis, which can help clinicians in providing a suitable treatment for HIV. J. Med. Virol. 86:394–403, 2014. © 2013 Wiley Periodicals, Inc.